STUDY TECHNOLOGY HAND LINE IN OCEAN FISHING PORT BUNGUS PROVINCE WEST SUMATRA - Rama Agus Mulyadi; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conductedinMai 2013inOceanFishingPort Bungus, Province West Sumatra. The aim of this study was to determine the construction and operation of the hand line, as well as the feasibility. The method used in this study is asurvey method. The results of the business analysis calculations indicate that the hand line gives benefit to fishermen and deserves to be developed due to the value of the benefit cost ratio is obtained at 2.0 while the financial rate of returnis 68,1% and payback period of capital is 17 month.Key words : construction and operation of the hand line